From thought to action: portrait of Natalio Berman B., Physician, Politician and Writer - Schonhaut Berman, Luisa (Cuadernos Judaicos, 2020)
Natalio Berman B. was a congressman, physician, public health advocate and writer. At the age of 8 he immigrated with his family from czarist Russia and quickly integrated into Chilean society. As the Jewish community in Chile started to develop, he led several Jewish and Zionist organizations. He later became one of the first 3 Jewish members of parliament in Chile, representing the socialist party. He joined the Communist party but renounced it in 1952 citing ideological disagreements. Berman came from a humble background of immigrants. His short life, marked by the struggle for social justice as a “non-conformist” paralleled the historic events of the first part of the XX’s century, He counted among his close friends Chilean presidents Aguirre Cerda and Gonzalez Videla and among his comrades the future President Salvador Allende and Nobel laureate Pablo Neruda. His extraordinary life came to a premature end on1957, at age 48. During Chile’s military period his legacy laid dormant, but new interest including research by his descendants and other scholars has shed new light on his life and legacy. This profile is gleaned from autobiographic, political and philosophical accounts of his life and work.